K-shell ionization of V, Cr, Mn, Fe, Co, Ni and Cu by 5-12 MeV carbon ions - Fazinić, S. (2014)
Nuclear Instruments and Methods in Physics Research, Section B: Beam Interactions with Materials and Atoms